Manufacturing integration: a systems engineering perspective. (11th May 2004) - Ip, W.H.; Ng, K.C.; Lee, T.C.; Tseng, C.
In this paper, the authors propose a conceptual model that aims to increase the competitiveness of a company though a systems engineering approach. This process which the company adopted to enhance its manufacturing system in a step-by-step manner is elaborated. Central to the strategy is the implementation of an integrated manufacturing system through the application of a systems engineering approach. The detailed design and implementation of the system is conducted through the systematic manufacturing strategic analysis. The integration process encompasses various elements such as Total Quality Management (TQM), Manufacturing Resources Planning (MRPII) and Real Time Monitoring System (RTMS). It emphasises not only the use of appropriate modern technology but also the management of technological change. In this paper, the model is used to describe the integration process. The detailed implementation is also documented using the proposed implementation process model. By adopting the integrated manufacturing system, and through continuous improvement, the productivity and hence profit of the company is increased. It is anticipated that the use of the systems engineering approach to design and implement manufacturing systems make an important contribution towards research into manufacturing strategy.